Prevalence of a History of Metabolic or Hypertensive Pregnancy Disorder in Patients With Myocardial Infarction and Non-obstructive Coronary Arteries: An Observational Cohort Study - Pustjens, Tobias F. S.; Vranken, Nousjka P. A.; Jansen, Gwyneth; Winkler, Patty J. C.; Stein, Mera; Hoebers, Loes; Kietselaer, Bas; Spaanderman, Marc E. A.; Rasoul, Saman; Ghossein-Doha, Chahinda; van 't Hof, Arnoud W. J. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Myocardial infarction with non-obstructive coronary arteries (MINOCA) predominantly affects younger females. Women with a history of gestational hypertension (GH), preeclampsia (PE), and gestational diabetes mellitus (GDM) are subjected to an elevated lifetime risk of cardiovascular disease. However, data on the potential association between these obstetric complications and MINOCA is lacking. Therefore, the current study aimed to provide insight in the prevalence of metabolic and hypertensive pregnancy disorders (MHPD) in MINOCA patients and their clinical characteristics. Methods: In this prospective, observational cohort study conducted at the Zuyderland Medical Center and Maastricht University Medical Center in the Netherlands, patients were enrolled if they were identified as having MINOCA. Data on individual patient characteristics, laboratory results, electrocardiography as well as (non-)invasive imaging procedures were derived from the electronic health record system. Patients were asked to complete a questionnaire about prior MHPD including GDM, GH, and PE. Patients were grouped into those with MHPD and those with prior uncomplicated normotensive pregnancy (or pregnancies)(NP). Results: After excluding male patients (n=63) and those without 1-year follow-up (n=53) from the 202 enrolled MINOCA patients, 86 female MINOCA patients remained eligible for analysis. Of the total female population, 25 (29.1%) patients had MHPD, including GH (n=19; 22.1%), PE (n=4; 4.7%), and GDM (n=7; 8.1%). The MHPD patients showed higher rates of chronic hypertension (84.0% vs. 55.7%; p=0.013), hypercholesterolemia (64.0% vs. 34.4%; p=0.012), a family history of CVD (84.0% vs. 45.9%; p=0.001), gout or rheumatic arthritis (16.0% vs. 1.6%; p=0.024), and were more often non-smokers (45.8% vs. 78.3%; p=0.004), compared to the NP patients. Moreover, MHPD patients were more likely to use cardiovascular medications at baseline. A specific cause for the MINOCA event was lacking more often in MHPD patients compared to the NP group, although borderline significant (64.0% vs. 42.6%, p=0.072). Conclusion: A history of metabolic and hypertensive pregnancy disorders occurred in one-third of female MINOCA patients. In these patients, conventional cardiovascular risk factors were more prevalent compared to NP patients. In most MHPD patients, the specific cause for MINOCA remained unclear.